Existence Results for Solutions of Integral Boundary Value Problems on Time Scales - Erbil Cetin; F. Serap Topal (Abstract and Applied Analysis)
This paper deals with the existence of solutions for integral boundary value problems (IBVPs) on time scales. We provide sufficient conditions for the existence of solutions by using Schauder fixed point theorem in a cone. Existence result for this problem is also given by the method of upper and lower solutions.